The mechanical heart valve TTK Chitra is inexpensive and of proven effectiveness (widely used in India and then in Nepal) - Kumar, Vasanth; Yadav, Umesh; Kumar, Awan; Vijaylakhsmi, - (Medical Journal of Eastern Nepal, 2022)
TTK Chitra heart valve prosthesis (chvp), a tilting disc mechanical heart valve of low cost and proven efficacy, has been in use for the last 15 years in India. Although various studies substantiating its long-term safety and efficacy are available but is less commonly used in Nepal. The TTK Chitra heart valve has been developed and widely used in India.